Geomorphological mapping of Messogia plain (East Attica, Greece). - Skentos, A.; Liosis, N.; Pavlopoulos, K. (Bulletin of the Geological Society of Greece, 2013)
This study concerns the geomorphological mapping of the area included in the map sheets Koropi and Plaka of the Hellenic Military Geographical Service map distribution in scale 1:50.000. This is an extensive area of East Attica which presents a complex terrain and a wide variety of landforms, due to its intense tectonism and the natural processes that shaped its morphology. The primary data that were used in the creation of the map mainly included geological and topographic maps, from which thematic layers of the topography, hydrography and geology were constructed through GIS processes. A Digital Elevation Model was also constructed, from which the slope and aspect maps were created. The thematic maps of slοpe and lithology were classified into categories, which were combined to constitute detection criteria of landforms. Decisive contribution in mapping was provided by the available orthophotomaps and aerial photographs, as well as the field work. Finally, with the appropriate combination of colors and symbols the geomorphological map of the study area was produced.